Inflammation-related research within the field of bladder cancer: a bibliometric analysis - Deng, Zhixuan; Tang, Ning; Xiong, Wanyan; Lei, Xu; Zhang, Tengfei; Yang, Ning (Frontiers in Oncology, 2023)
Abstract: Background: In recent years, the link between inflammation and bladder cancer (BC) has received much attention. However, there were no relevant bibliometric studies to analyze the inflammation-related research within this field of BC. Methods: We selected Web of Science Core Collection (WOSCC) as the data source to obtain articles and reviews on inflammation-related research within the field of BC from WOSCC's inception to October 10,2022. The collected data were meticulously and manually screened, after which we used VOSviewer, CiteSpace, Biblioshiny and an online analysis platform (https://bibliometric.com/) to perform bibliometric analysis on the data and visualize the results. Results: A total of 4301 papers related to inflammation-related research within this field of BC were included in this study.The number of publications has steadily increased over the last decades (R²=0.902). The top contributing country was the United States, O'Donnell, Michael A was the most published authors, the leading contributing institution was the University of Texas, and the leading contributing journal was JOURNAL OF UROLOGY. The keywords co-occurrence analysis indicated that“immunotherapy,”“inflammation-related biomarkers,” and “tumor microenvironment” were the hot spots and frontiers of research in this field. Conclusion: This study clarifies the contribution of countries, institutions, authors, and journals in inflammation-related research within this field of BC through a bibliometric approach and identifies research hotspots and frontiers in the field. Notably, these findings can help researchers to understand more clearly the relationship between inflammation and BC.